2017
DOI: 10.4103/jnsbm.jnsbm_29_17
|View full text |Cite
|
Sign up to set email alerts
|

Association of neck circumference and obesity with blood pressure among adolescents in urban and rural population in North Tamil Nadu

Abstract: Aim:Since a few studies exist on the association of neck circumference (NC) and obesity with blood pressure (BP) among adolescents in India, we found it highly relevant to measure the NC and body mass index (BMI) using them as indicators of upper body subcutaneous fat and obesity and relate them to BP in a rural and urban adolescent population in North Tamil Nadu.Materials and Methods:This is a community-based cross-sectional study of descriptive design where 500 students from urban and rural areas were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
1
9
0
2
Order By: Relevance
“…A study among Korean adolescents found that high BMI (>85th percentile) and high waist circumference (>90th percentile) were positively correlated with high SBP (>90th percentile) in both sexes and high DBP (>90th percentile) in boys [45]. A community-based crosssectional study reported that an increase in SBP and DBP was correlated with an increase in neck circumference and BMI [46]. From the United States of America, findings showed that odds ratios for elevated BPs were higher in children with wide neck circumference than those with normal neck circumference.…”
Section: Discussionmentioning
confidence: 99%
“…A study among Korean adolescents found that high BMI (>85th percentile) and high waist circumference (>90th percentile) were positively correlated with high SBP (>90th percentile) in both sexes and high DBP (>90th percentile) in boys [45]. A community-based crosssectional study reported that an increase in SBP and DBP was correlated with an increase in neck circumference and BMI [46]. From the United States of America, findings showed that odds ratios for elevated BPs were higher in children with wide neck circumference than those with normal neck circumference.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the interdisciplinary therapy was effective in reducing waist, neck, hip, and abdominal circumferences. These circumferences are positively correlated with cardiovascular risks, obesity, and metabolic syndrome; and the improvement of these anthropometric indicators are important in controlling obesity and cardiovascular diseases (61, 67, 68, 7074).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the included articles carried out a cross-sectional design, except for one case-control [ 45 ] and one prospective study [ 46 ]. According to the geographical region, seven of the studies were set out in Europe [ 7 , 14 , 24 , 27 , 29 , 32 , 45 ], eight in America [ 25 , 26 , 33 , 35 , 39 , 40 , 41 , 42 ], eight in Asia [ 28 , 30 , 31 , 34 , 38 , 43 , 44 , 46 ], and three in Africa [ 23 , 36 , 37 ]. Based on the anthropometric indicator, 19 articles approached NC, seven articles WrC, and two studied both anthropometric indicators [ 28 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the anthropometric indicator, 19 articles approached NC, seven articles WrC, and two studied both anthropometric indicators [ 28 , 31 ]. Furthermore, 14 articles recruited subjects at public schools [ 7 , 23 , 26 , 28 , 29 , 30 , 31 , 32 , 33 , 38 , 40 , 42 , 44 , 45 ] and 12 articles at outpatient clinics [ 14 , 24 , 25 , 27 , 34 , 35 , 36 , 37 , 39 , 41 , 43 , 46 ]. Most studies included schoolchildren and adolescents with age ranges between 5 and 18 years, except for one study that included 3-year-old preschool children [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation